Wireless sensor networks: current status and future trends - Khan, Shafiullah (CRC Press, USA, 2012)
Human sensing is one way of collecting information, acquiring knowledge and making reliable decisions. Wireless Sensor Networks (WSNs) imitate this human intelligence capability, but on a wider distributed scale, with faster, cheaper and more effective ways that can be used for different applications. Recognizing this fact, we decided to introduce this book on WSNs that documents the current state of these networks, and their future trends.